1987
DOI: 10.1111/j.1151-2916.1987.tb04963.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Titanates: Stoichiometry and Raman Spectra

Abstract: March 1987Thus, on gradual addition of silica sol to A13' sol during gelation and the subsequent heating, Si-A1 spinel will form with association of amorphous aluminosilicate phase. The composition and amount of the amorphous phase will be expected to change with such additions. As a result, the observed 0.139-nm peak area (Table 11) is found to decrease with increasing percent of SiOz instead of remaining more or less constant and equal to the area of the standard y-Alz03. Therefore, any attempt to prepare pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
62
0
4

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 11 publications
10
62
0
4
Order By: Relevance
“…The Raman spectrum of bulk Na 2 Ti 3 O 7 (curve c) and Na 2 Ti 6 O 13 (curve d) are similar to those reported in the literature. [33][34][35] Again the relative number of modes observed for Na 2 Ti 3 O 7 and Na 2 Ti 6 O 13 are in agreement with group theory predictions. We observed that both NTTiOx and NRTiOx have different Raman spectra with respect to the number of bands, but they are similar with regard to location of energy bands.…”
Section: Vibrational Propertiessupporting
confidence: 84%
“…The Raman spectrum of bulk Na 2 Ti 3 O 7 (curve c) and Na 2 Ti 6 O 13 (curve d) are similar to those reported in the literature. [33][34][35] Again the relative number of modes observed for Na 2 Ti 3 O 7 and Na 2 Ti 6 O 13 are in agreement with group theory predictions. We observed that both NTTiOx and NRTiOx have different Raman spectra with respect to the number of bands, but they are similar with regard to location of energy bands.…”
Section: Vibrational Propertiessupporting
confidence: 84%
“…According to the Raman spectra in the literature [27], the sharp peaks labeled with numbers in Fig. 2 belong to K 2 Ti 6 O 13 , which is sensitive to Raman spectroscopy [28,29]. However, the corresponding peaks in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at high frequency is attributed to the short Ti-O stretching vibration with non-bridging oxygen atoms coordinated to the interlayer cation. 25 This peak is located at higher frequencies for the sodium form compared to the potassium one, shifting from 880 to 900 cm -1 , meaning that the bond has become shorter. In addition, the peak at 235 cm -1 which corresponds to the Ti-O-K vibration 26 in K 0.8 Ti 1.73 Li 0.27 O 4 changed after the ion exchange and split into several overlapping peaks in the Na ion-exchanged sample.…”
Section: Chemical and Structural Characterizationmentioning
confidence: 99%